The Relationship Between Residential Density and Ventilation Area and The Incidence of Pulmonary TB in The Work Area of The Temindung Community Health Center - Rusdi; Ainur Rachman; Dito Julianto A (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Tuberculosis (TB) is an infectious disease that remains a major health problem in Indonesia. One of the important risk factors in its transmission is the condition of the residential environment, including residential density and the area of ​​​​house ventilation. Objective: This study aims to analyze the relationship between residential density and ventilation area with the incidence of pulmonary TB in the working area of ​​​​Temindung Community Health Center, Samarinda City. Research Methods: This study used a quantitative approach with a case-control design. The study sample consisted of 90 respondents, namely 45 pulmonary TB cases and 45 non-TB controls taken from the working area of ​​​​Temindung Community Health Center. Data were collected through direct observation, interviews, and measurements using a rollmeter. Analysis was carried out bivariately using the Chi-Square test and Odds Ratio (OR). Results: The results of the analysis showed a significant relationship between ventilation area and the incidence of pulmonary TB (p = 0.001; OR = 5.091; 95% CI: 2.052–12.628). In contrast, no significant association was found between residential density and the incidence of pulmonary TB (p = 1.000; OR = 0.780; 95% CI: 0.195–3.118). Conclusion: Inadequate ventilation is a significant risk factor for the incidence of pulmonary TB. Meanwhile, residential density was not statistically proven to be associated with the incidence of pulmonary TB in the study area. Environmental health interventions that emphasize improving home ventilation are recommended to reduce the incidence of pulmonary TB.